Phenotypic Screening of Ds Transposon and Activation-tag Insertional Mutant Rice Population for Drought and Salinity Tolerant Related Traits - Nugroho, Satya; Zannati, Anky; Situmorang, Apriadi; Windiastri, Vincentia Esti; Widyajayanti, Dwi; Pantouw, Carla Frieda; Astuti, Dwi; Indrayani, Sri; Rachmawati, Syamsidah; Mulyaningsih, Enung Sri; Santoso, Tri Joko; Trijatmiko, Kurniawan Rudi (BRIN, 2011)
The studies of rice genes through functional genomics are greatly facilitated by the availability of the complete genome sequences, including the complete physical map of the japonica rice cv. nipponbare. Using the Ac and Ds transposon, that are capable of transposition in various heterologous plants including the monocotyledon rice, combined with the enhancer element for generating activation taged lines, it is possible to discover and isolate functional genes involved in various important agronomical traits; such as those involved in abiotic stress tolerance (drought, high salt) and biotic stresses diseases and pests. We have developed 1,785 first (T0) generation of mutant nipponbare rice by transposons Ac/Ds insertions containing activation-tag, generated by transformation using Agrobacterium-mediated method. Currently, we have generated approximately 1,000 stable lines with transposon Ds and activation-tag insertion ready for screening. Efficient screening methods for mutant Nipponbare rice lines have been established for agronomically important mutant traits. Among the new phenotypes related to important agronomical traits observed were drought and salt tolerant or sensitive, stunted and robust growth, variable root penetration and other interesting traits such as reduced tillering, rolled leaf and thin tiller.